The allocation of interstate ground water: evaluation of the Republican River Compact as a case study - Knox, Kenneth W., author (Colorado State University. Libraries, 2004)
Management of water resources is a demanding and complex challenge. The complexity is magnified when the source of water supply transcends local jurisdictions and extends across state boundaries to include multiple political interests, management authorities, and legal parameters. Interstate river compacts are used in the United States as an effective legal and administrative instrument to equitably distribute water within a multi-state river system. Of the forty-five interstate river compacts in the United States that focus upon the distribution of water supplies, only six include ground water within the distribution system -- even though ground water is an important and often the dominant source of water supply that is used within an interstate river basin.

The goals of this dissertation are to examine the reasons why ground water is not included within an interstate river compact allocation system and to identify factors that show how this omission may be rectified. The primary research objective is to identify and examine the quantitative and qualitative data necessary to construct a template of factors and issues that warrant consideration in the decision-making process of compact administration officials who are contemplating the inclusion of ground water within a compact’s allocation system.

The research uses a case study and program evaluation methodology to systematically analyze the integrated processes associated with complex interstate river compact administration in a comprehensive manner. The Republican River Compact is examined as an institutional model because it is representative of most other interstate river compacts that allocate surface water supplies only. Evaluation of the Republican River Compact also provides unique insight into the decision-making processes, and consequences, that pertain to the consideration, deferral, and ultimate inclusion of ground water within an interstate river compact allocation system. Although the use of a case study in engineering research differs from traditional quantitative approaches, it offers a distinct and valuable research design to address the non-numeric and qualitative data that is used in the decision-making process by water resources engineers.

The research findings clearly indicate that ground water may be successfully incorporated within the allocation system of an existing interstate river compact. The findings also indicate the Republican River Compact Administration has been effective in promoting the efficient and beneficial use of water within the Republican River Basin since 1943. The research shows the use of a case study and program evaluation methodology is an appropriate and effective approach for addressing the complex problems and decision-making processes inherent in interstate river compact administration.
Keywords: Civil engineering; Area planning and development; Public administration